Menopausal transition and early postmenopause in women with obesity of various types and degrees - Sandakova E.A; Zhukovskaya I.G (LCC «Medicine-Inform», 2019)
Menopausal transition and early postmenopause in women with obesity of various types and degrees E.A. Sandakova1, I.G. Zhukovskaya2 1 Academician E.A. Wagner Perm State Medical University, Perm, Russian Federation 2 Izhevsk State Medical Academy, Izhevsk, Russian Federation Aim: to assess the features of menopausal transition and early postmenopause in women with overweight or obesity of various types and degrees. Patients and Methods: 139 women were examined. Group I (study group) included 109 women with overweight or obesity. Group II (control group) included 30 women at a normal weight with waist circumference less than 80 cm. 65% of group I women and 56.6% of group II women were in menopausal transition, the others were in postmenopausal period (less than 3 years). Outpatients' record analysis, health questioning, medical and gynecological examination, vaginal microbiocoenosis evaluation (by microscopy), pelvic ultrasound, and blood biochemistry (i.e., alanine aminotransferase, aspartate aminotransferase, urea, fibrinogen, cholesterol, high- and low-density lipoproteins, triglycerides, glucose, insulin, glycated hemoglobin, insulin resistance indices HOMA and Caro) were performed. Menopause symptoms were assessed by the Greene climacteric scale. In addition, all women were examined by a physician, a cardiologist, and an endocrinologist. Results: visceral obesity was predominant in menopausal transition and early postmenopause. This obesity type is characterized by high cardiovascular comorbidity, i.e. arterial hypertension (36%), ischemic heart disease (22%), gastrointestinal disorders (chronic gastritis, 62.4%; chronic colitis, 18.3%; chronic pancreatitis, 28.4%), metabolic disorders (type 2 diabetes, 16%; cholelithiasis, 42%). Climacteric syndrome in obese women is more severe due to the headaches (95% of patients), excitability (72.5%), sleep disturbances (67.5%), muscle and joint pains (62.5%), and sexual dysfunctions (52.4%). Conclusion: menopausal disorders in overweight and obese women who visit a doctor many times are generally ignored. There are neither interdisciplinary interactions nor systemic approach to the management of these patients. Key words: menopausal transition, early postmenopause, climacteric syndrome, gluteofemoral obesity, abdominal obesity. For citation: Sandakova E.A., Zhukovskaya I.G. Menopausal transition and early postmenopause in women with obesity of various types and degrees. Russian Journal of Woman and Child Health. 2019;2(1):16-22.